Preparation of Active Food Packaging and Coating Material Based on Bacterial Cellulose to Increase Food Safety - Joko Sulistyo; Prasetyon Sepsi Winarno; Ika Yohanna Pratiwi; Lorent Permata Ridfan; Katherine Mahadewi Pranata; Raja Munirah Raja Chick (Jurnal Teknologi dan Industri Pangan, 2023)
The use of bacterial probiotic metabolite-based active-packaging and coatings is an innovative approach that has gained widespread attention worldwide. Additionally, its utilization can lead to improvements in qualities and properties of food products. This study was aimed to develop a food spoilage prevention system using active food packaging and coating material in preventing food spoilage while increasing its shelflife. The materials used were bacterial cellulose (BC) based bioplastics fortified with fermented soymilk extracts (FSME) using Lactobacillus acidophilus as the producer of the antimicrobial and antioxidant agents. Moreover, the applications of FSME containing probiotic bacterial metabolites are discussed to highlight their efficacy in enhancing the quality and shelf life of food products.The antimicrobial test showed that the FSME could inhibit the growth of pathogenic microbial cultures at minimum inhibitory concentration (MIC) of 10% (v/v) as shown by clear zones, around colonies of E. coli (14.33±0.58 mm), S. aureus (18.33±6.03 mm), S. Typhimurium (11.67±1.15 mm), L. monocytogenes (11.33±2.31 mm), and B. cereus (13.33±3.06 mm). Meanwhile the results of IC50 for antioxidant activity test (µg/mL) indicated that the FSME showed radical scavenging activity against DPPH at approximately 75.27±2.552 (2.5%, v/v), 55.00±0.791 (5.0%, v/v), 43.17±1.603 (7.5%, v/v) and 15.05±0.346 (10%, v/v), respectively. The shelflife of strawberries coated with the active food coating using the bioplastic fortified with FSME showed an increase in shelf life of 14 days at 4°C. The overall results indicated that the use of BC based bioplastics fortified with FSME can play an important role in preventing premature spoilage and increasing the shelf life of food products.